Biomechanical Analysis Forehand Groundstroke Technique On Field Tennis: A Review Of The Literature - Muh Nugrah Setyawan; Agus Sutriawan (STAMINA, 2026)
The forehand groundstroke is one of the fundamental techniques in tennis that requires complex coordination of the musculoskeletal system. This study aims to systematically analyze the biomechanics of forehand groundstroke technique, including movement phases, segmental body contribution, racket velocity, racket-face angle at impact, and its implications for performance improvement and injury prevention. The research method used a systematic literature review approach by analyzing peer-reviewed journals, textbooks, and relevant academic sources related to tennis biomechanics. The results of the review show that the forehand groundstroke consists of five main phases: initiation, preparation, acceleration, impact, and follow-through. Quantitative findings indicate that racket velocity reaches its peak during the impact phase, with professional players producing racket speeds of approximately 25–35 m/s. Stroke power is generated through sequential segmental contribution involving the lower limbs, trunk, shoulder, upper arm, forearm, and wrist. Kinematic analysis also shows that torso rotation and shoulder external rotation play important roles in increasing racket speed and stroke effectiveness. In addition, the racket-face angle at impact significantly influences ball direction, accuracy, and control. This study concludes that a comprehensive understanding of forehand groundstroke biomechanics can help coaches and athletes optimize technique, improve stroke performance, and reduce the risk of injury. The findings provide practical recommendations for developing more effective tennis training programs based on biomechanical principles